Japanese encephalitis - Wiwanitkit, Viroj (Journal of Pediatric Infectious Diseases, 2007)
Japanese encephalitis (JE) is an important mosquito-borne infection. As a zoonosis, JE cannot be eradicated, but reduction of the human disease burden can be achieved through routine childhood vaccination in endemic countries, which is a low cost, high benefit measure. This article will review the worldwide epidemiology, vector transmission, genetics and molecular biology of JE, as well as present the pathophysiology, clinical manifestations and complications, diagnosis, treatment and prevention of JE.
Keywords: Japanese encephalitis